Avaliação do cumprimento da norma brasileira de comercialização de alimentos para lactentes e crianças de primeira infância, bicos, chupetas e mamadeiras (NBCAL) na cidade de João Pessoa - Silva, Talita Maria Alves Lopes da (2023)
The International Code of Marketing of Breast Milk Substitutes was promulgated by the World Health Organization in 1981 in response to the decline in breastfeeding (BF) rates around the world, aiming to control the marketing of infant formula and other products used as breast milk substitutes. human milk. In Brazil, the Code was adopted as Law (nº 11,265) in 2006, but this law has never been systematically evaluated in the national territory. This study was part of a multicenter project that was carried out in the capitals of five Brazilian states: Rio de Janeiro, São Paulo, Distrito Federal, Paraíba, Santa Catarina, and a city in the interior, Ouro Preto/MG. Approved by CNPq Notice nº 13/2017, its objective was to evaluate compliance with this law in commercial establishments and the knowledge of it by the managers of these establishments. The objective was also to evaluate maternal perception about this law. For this purpose, a qualitative study was carried out using the open interview technique with 14 mothers of children under three years of age recruited through the snowball sampling method. A survey was also carried out in commercial establishments with the application of a structured questionnaire that would identify compliance or not with the law. 204 establishments were evaluated in João Pessoa. With regard to infringements of the NBCAL, 60.3% of establishments presented infringements. The commercial strategy of special product exhibition was the most practiced (43.6%), followed by price promotion (39.2%). The data from the present study suggest that commercial professionals responsible for organizing and distributing products that are within the scope of the law are aware of the legislation, as among the establishments visited, a smaller proportion (30.9%) practiced commercial promotion for which the law does not allow. On the other hand, we have a lack of knowledge about NBCAL on the part of managers and pharmacists, professionals who guide mothers in their choices and who can encourage them to use products that compete with BF. The mothers' interviews were evaluated using discourse analysis and “word cloud” methods and reflect how vulnerable this group is and has been the target of information that discourages and can lead to the interruption of breastfeeding. The mothers' audios carry information that care for them needs to be reinforced to protect BF. Interventions to improve this situation must be multilevel, not just aimed at mothers and health professionals, so that the entire population is aware of the legislation that protects BF and uses tools to enforce it.